Incorporation rate of recycled aggregates in cement raw meals. (10th July 2020) - Krour, Hichem; Trauchessec, Romain; Lecomte, André; Diliberto, Cécile; Barnes-Davin, Laury; Bolze, Breffni; Delhay, Arnaud
Highlights: The chemical composition of mixed and recycled concrete aggregates varies widely. This variability affects their incorporation rates in cement raw meal. Their incorporation in cement raw meal affected slightly the burning process. The incorporation rates of RAs in cement raw meals vary mainly from 10% to 20%. Abstract: Incorpoaration of recycled aggregates (RAs) into cement raw meals (CRMs) can be a complementary application for construction and demolition wastes (CDWs) preserving natural resources. However, the variability of CDW chemical composition and cement plant specifies require to adapt the incorporation rate on a case-by-case basis. This study presents a chemical and mineralogical characterization (X-Ray diffraction/fluorescence and thermal analyzes) of eight CDWs from different categories and origins. Laboratory clinkers syntheses show that these recycled materials affect slightly the raw meal burnability and the clinker composition mostly likely due to their mineralogical composition (quartz and feldspars contents). These results supplemented by literature review allow discussing the incorporation rates depending on three parameters: the RAs composition, the cement type and the cement quarry composition. This paper provides new insights concerning the use of recycled aggregates in cement raw meal, and shows that the maximum incorporation rate is mainly between 10-20% (50% of the 180 raw meal calculations), occasionally lower than 5% (13%) or higher than 30% (17%). Given the RAs incorporation effect (marl replacement, quartz proportion, etc.), it is even recommended to keep a rate below 10%.